2023
DOI: 10.1002/ohn.166
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 Effects on Psychophysical Olfactory Scores: Prospective Study With Evaluation Before and 60‐Days After Infection

Abstract: The aim of this study was to prospectively evaluate the olfactory function in a series of individuals infected with SARS-CoV-2 and who had undergone psychophysical olfactory assessment prior to infection. Individuals unexposed to SARS-CoV-2 infection underwent a psychophysical evaluation of smell with the Sniffin' Sticks test. The subjects were followed prospectively and included in the study if they developed SARS-CoV-2 infection with a second test 60 days after recovery. At the 60-day follow-up of the 41 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Secondly, the 60-day re-evaluation of controls who developed infection in the follow-up period found that although threshold, discrimination and identification scores returned to levels that classified individuals as normosmic, median T values were significantly lower than before infection. 60 This olfactory alteration, although unconscious and therefore not affecting quality of life, can expose patients to environmental dangers.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the 60-day re-evaluation of controls who developed infection in the follow-up period found that although threshold, discrimination and identification scores returned to levels that classified individuals as normosmic, median T values were significantly lower than before infection. 60 This olfactory alteration, although unconscious and therefore not affecting quality of life, can expose patients to environmental dangers.…”
Section: Discussionmentioning
confidence: 99%